Ewing sarcoma of the uterus: A case report - Zeynep Tek; Anya Laibangyang; Oluwole Odujoko; Bhavna Khandpur; David Doo (Elsevier, 2024)
A case is described of Ewing sarcoma of the uterus, an atypical presentation of an already rare cancer.A 55-year-old woman presented with abdominal pain, abnormal uterine bleeding and a uterine mass that measured 11 × 10 × 14.5 cm and demonstrated heterogeneous enhancement with possible areas of central necrosis, concerning for sarcoma. She had a complete surgical resection with total abdominal hysterectomy, bilateral salpingo-oophorectomy, omentectomy, bilateral pelvic lymph node dissection, and excision of mesenteric tumor implants. Her final pathology showed primary Ewing sarcoma-primitive neuroectodermal tumor of the uterus with metastatic spread to the peritoneal cavity. She finished 14 cycles of vincristine-doxyrubicin-cyclophosphamide-ifosfamide, etoposide chemotherapy with no evidence of recurrent metastatic disease at 6-month follow-up.Ewing sarcoma is a rare cancer, predominantly seen in adolescents, that typically are of the bone, although in rare instances it can arise from soft tissue; even rarer are presentations in the female genital tract. Even with typical presentations of Ewing sarcoma of the bone, metastatic disease has an overall poor prognosis. The scarcity of cases of metastatic Ewing sarcoma-peripheral neuroendocrine tumors of the uterus makes the condition especially difficult to study. This report describes a case of Ewing sarcoma of the uterus treated by complete surgical resection and aggressive multimodal chemotherapy.